2011
DOI: 10.1111/j.1467-8624.2011.01677.x
|View full text |Cite
|
Sign up to set email alerts
|

School Attendance Problems and Youth Psychopathology: Structural Cross‐Lagged Regression Models in Three Longitudinal Data Sets

Abstract: This study tests a model of reciprocal influences between absenteeism and youth psychopathology using three longitudinal datasets (Ns= 20745, 2311, and 671). Participants in 1st through 12th grades were interviewed annually or bi-annually. Measures of psychopathology include self-, parent-, and teacher-report questionnaires. Structural cross-lagged regression models were tested. In a nationally representative dataset (Add Health), middle school students with relatively greater absenteeism at study year 1 tende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
70
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 46 publications
4
70
0
2
Order By: Relevance
“…Thus, school absenteeism indicates the average percentage of school days missed by an average student during the school year. Although this measure does not distinguish between excused and unexcused absences, both types of absences are positively correlated (Burton, Marshal, & Chisolm, 2014) and total absenteeism is related to behavior problems and school dropout (Alexander, Entwisle, & Kabbani, 2001; Wood et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Thus, school absenteeism indicates the average percentage of school days missed by an average student during the school year. Although this measure does not distinguish between excused and unexcused absences, both types of absences are positively correlated (Burton, Marshal, & Chisolm, 2014) and total absenteeism is related to behavior problems and school dropout (Alexander, Entwisle, & Kabbani, 2001; Wood et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…School absenteeism is associated with myriad negative outcomes including social isolation, mood and conduct disorders, sleep disturbances, substance abuse, and longer term outcomes such as dropping out from school entirely (Eaton, Brener, & Kann, 2008; Egger, Costello, & Angold, 2003; Kearney, 1993; Wood et al, 2012). A longitudinal study of 9- to 16-year-olds found that, depending on the type of school absence (school refusal due to anxiety, unexcused or unexplained absence, and mixed school refusal behavior), 25% to 90% of those missing school met criteria for a diagnosis as defined by the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV; American Psychiatric Association, 1994), whereas less than 7% of those who did not miss school met criteria for a DSM-IV diagnosis (Egger et al, 2003).…”
mentioning
confidence: 99%
“…A longitudinal study of 9- to 16-year-olds found that, depending on the type of school absence (school refusal due to anxiety, unexcused or unexplained absence, and mixed school refusal behavior), 25% to 90% of those missing school met criteria for a diagnosis as defined by the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV; American Psychiatric Association, 1994), whereas less than 7% of those who did not miss school met criteria for a DSM-IV diagnosis (Egger et al, 2003). The directionality of these relations is often unclear, although analysis of large-scale longitudinal datasets has found somewhat more support for psychopathology leading to absenteeism rather than the other way around (Wood et al, 2012). These results suggest it is possible to use psychological measures to identify those at risk for skipping school before the onset of the behavior and therefore create an opportunity for preventive intervention.…”
mentioning
confidence: 99%
“…Randomization into the LIFT intervention or services as usual control groups was at the level of the school. Detailed study procedures are provided elsewhere (Eddy, Reid, Stoolmiller, & Fetrow, 2003; Reid, Eddy, Fetrow, & Stoolmiller, 1999; Wood et al, 2012) . At baseline, most children were in first or fifth grade.…”
Section: Methodsmentioning
confidence: 99%